(untitled) (World Economics and Finance Bulletin, 2024)
The research topic is relevant because the paper examines the idea of population social protection and strategies for enhancing the social protection mechanism. Several academics and writers provide scientific definitions of terms like "social protection" and "social policy" in this page. The paper also categorizes social protection programs, provides a thorough summary and analysis of the scientific and theoretical methods for enhancing their efficacy. The primary function of social protection is to alert vulnerable populations to potential financial issues or to offer social support to them. Every market economy has as one of its defining characteristics the understanding that each individual choose for themselves how to engage in the economy. The main responsibility for insurance is with each individual. In the event that an individual lacks social insurance, governmental social aid will safeguard his interim income. The success of state-implemented policies determines the stability of society, its sustained growth, and the social support of its members. In today’s world, the challenges facing economic growth are inextricably linked to the necessity to provide social issues—such as the establishment and enhancement of the population’s social security system—special consideration